Inovasi Pembelajaran Teknojarkom berbasis Game Android Meningkatkan Motivasi Peserta Didik SMK PGRI 2 Kertosono - Titik Dian Darmayanti (Universitas Darul Ulum, 2025)
The rapid growth of technology has revolutionized education, making it possible to incorporate technology into teaching and learning. Technology serves as a versatile learning medium, encompassing interactive learning materials, educational games, practice exercises, and comprehensive lessons accessible through various Android-based devices. In contrast, traditional classroom instruction often relies on textbooks, lectures, and examples, resulting in a less engaging and monotonous learning experience. The objective of this research is to develop innovative and efficient learning media that foster increased student interest and understanding, particularly in the realm of computer networks within the informatics curriculum. This research utilizes the R&D framework to produce and test educational materials. The development process consists of nine stages: Needs Analysis, Design Planning, Design Implementation, Testing, Expert Validation, Media Revisions, School-Based Feasibility Testing, and Media and Product Improvement. This media game is designed with three different levels of difficulty, each covering different computer network material, namely basic computer networks, IP addresses, and types of computer networks. The research outcomes demonstrate that the the development of android based computer network educational game learning media has succeeded in offers easy accessibility. This interactive game-based learning tool enables students to engage in both play and learning of computer network technology in a more enjoyable and effective manner. Moreover, it provides numerous advantages for teachers, including increased student interest in learning and a more interactive and engaging classroom environment.